Optimization of dose and route of administration of the P‐glycoprotein inhibitor, valspodar (PSC‐833) and the P‐glycoprotein and breast cancer resistance protein dual‐inhibitor, elacridar (GF120918) as dual infusion in rats. Issue 2 (4th March 2021) - Rowbottom, Christopher; Pietrasiewicz, Alicia; Tuczewycz, Taras; Grater, Richard; Qiu, Daniel; Kapadnis, Sudarshan; Trapa, Patrick
Abstract: Transporters can play a key role in the absorption, distribution, metabolism, and excretion of drugs. Understanding these contributions early in drug discovery allows for more accurate projection of the clinical pharmacokinetics. One method to assess the impact of transporters in vivo involves co‐dosing specific inhibitors. The objective of the present study was to optimize the dose and route of administration of a P‐glycoprotein (P‐gp) inhibitor, valspodar (PSC833), and a dual P‐gp/breast cancer resistance protein (BCRP) inhibitor, elacridar (GF120918), by assessing the transporters' impact on brain penetration and absorption. A dual‐infusion strategy was implemented to allow for flexibility with dose formulation. The chemical inhibitor was dosed intravenously via the femoral artery, and a cassette of known substrates was infused via the jugular vein. Valspodar or elacridar was administered as 4.5‐hour constant infusions over a range of doses. To assess the degree of inhibition, the resulting ratios of brain and plasma concentrations, Kp's, of the known substrates were compared to the vehicle control. These data demonstrated that doses greater than 0.9 mg/hr/kg valspodar and 8.9 mg/hr/kg elacridar were sufficient to inhibit P‐gp‐ and BCRP‐mediated efflux at the blood‐brain barrier in rats without any tolerability issues. Confirmation of BBB restriction by efflux transporters in preclinical species allows for subsequent prediction in humans based upon the proteomic expression at rodent and human BBB. Overall, the approach can also be applied to inhibition of efflux at other tissues (gut absorption, liver clearance) or can be extended to other transporters of interest using alternate inhibitors. Abstract : Optimization of chemical inhibitors for P‐gp and BCRP at the BBB.